Pergumulan Kalam Dan Falsafah “Yang Tak Kunjung Usai”: Sebuah Bacaan Kritis Pemikiran Muhammad Abid Al-Jabiri - Febri Hijroh Mukhlis (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2018)
Islamic theology and philosophy have dynamically encountered. Based on historical trace, they have built a fundamental scientific perspective. Nowadays, they have to continue interacting in critical and contributive way for the future civilization development. They cannot opposite each other and have to be in common ground in scientific methodological framework. They have now an important role in responding new issues in social, humanities, and also cultural.